2014
DOI: 10.1089/apc.2013.0373
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Poor Respiratory Health Status in Adults Living with Human Immunodeficiency Virus Infection

Abstract: The increased longevity afforded by combination antiretroviral therapy in developed countries has led to an increased concern regarding senescence-related diseases in patients with human immunodeficiency virus (HIV) infection. Previous epidemiologic analyses have demonstrated an increased risk of chronic obstructive pulmonary disease, as well as a significant burden of respiratory symptoms in HIV-infected patients. We performed the St. George's Respiratory Questionnaire (SGRQ) in 199 HIV-positive men, and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
1
19
0
1
Order By: Relevance
“…This is important, as lung function impairment can correlate poorly with symptoms and functional status 10. We sought, therefore, to provide a comprehensive analysis of existing data regarding respiratory symptoms in people living with HIV with the aim of understanding how this might have changed with ART, and where deficiencies in the current evidence base exist.…”
Section: Introductionmentioning
confidence: 99%
“…This is important, as lung function impairment can correlate poorly with symptoms and functional status 10. We sought, therefore, to provide a comprehensive analysis of existing data regarding respiratory symptoms in people living with HIV with the aim of understanding how this might have changed with ART, and where deficiencies in the current evidence base exist.…”
Section: Introductionmentioning
confidence: 99%
“…1 For patients infected with HIV, the prevalence of COPD is likely higher and is an increasing cause of poor respiratory health and death in this population. [2][3][4] This increase in COPD is thought to be due to an increased prevalence of smoking in patients with HIV/ AIDS [5][6][7][8][9][10][11][12] in combination with a detrimental amplified inflammatory response in the lungs of those exposed to toxins in cigarette smoke. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Patients with HIV/AIDS also have increased barriers to smoking cessation, which adds to the risk for COPD over time.…”
mentioning
confidence: 99%
“…19,24 Studies show that in addition, HIV infected patients with higher HIV viral loads or lower CD4 T-cell counts have more rapid decline in pulmonary function, worse disease, and likely worse diffusing capacity than similar patients without HIV. 2,4,31,32 Whether peak flow is influenced by these factors in a similar manner remains less clear.…”
mentioning
confidence: 99%
“…Two previous reports used the SGRQ to evaluate respiratory health in HIV-positive adults: Hirani et al evaluated 98 consecutive HIV-positive individuals (84% male) attending HIV care services in Philadelphia, USA, and found a mean SGRQ Total score of 7 [22]; in contrast, Leung et al reported a mean SGRQ Total score of 32 in 199 HIV-positive men attending care services in Vancouver, Canada [9]. Our data therefore provide the first estimate of the difference in respiratory health (as experienced by individuals) between HIV-positive adults with optimized access to ART and HIV-negative adults.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most studies assessing respiratory health in HIV-positive populations have focused on objective measurements of lung function (such as spirometry) rather than the subjective impact of respiratory impairment on health-related quality of life [5,8]. This is an important issue, as respiratory symptoms can correlate poorly with objectively measured lung function [9], yet may have a significant effect on quality of life. There is a need, therefore, to better understand the degree to which PLWH with access to effective ART have worse respiratory health than HIVnegative individuals (with similar risk factors), and the impact of this on their quality of life [10].…”
Section: Introductionmentioning
confidence: 99%